Post-Angiography Contrast-Induced Encephalopathy (Bangladesh Critical Care Journal, 2015)
The use of radio-contrast agents are increasing day by day in modern imaging modalities. But they are not completely risk free. Among others, contrast-induced encephalopathy is a rare adverse effect. We report a patient with end-stage renal disease developing contrast induced encephalopathy following coronary angiogram (CAG).Bangladesh Crit Care J September 2014; 2 (2): 85-86